Leishmania donovani induced Unfolded Protein Response delays host cell apoptosis in PERK dependent manner. - Kumar Abhishek; Sushmita Das; Ashish Kumar; Ajay Kumar; Vinod Kumar; Savita Saini; Abhishek Mandal; Sudha Verma; Manjay Kumar; Pradeep Das (Public Library of Science (PLoS), 2018)
BACKGROUND:Endoplasmic reticulum (ER) stress generated unfolded stress response (UPR) is a basic survival mechanism which protects cell under unfavourable conditions. Leishmania parasite modulates host macrophages in various ways to ensure its survival. Modulation of PI3K-Akt pathway in delayed apoptotic induction of host; enables parasite to stabilize the infection for further propagation. METHODOLOGY:Infected RAW macrophages were exposed to campothecin or thagsigargin and phosphorylation status of PERK, Akt, BAD and Cyt-C was determined through western blotting using phospho specific antibody. Expression at transcriptional level for cIAP1 &2, ATF4, CHOP, ATF3, HO-1 and sXBP1 was determined using real time PCR. For inhibition studies, RAW macrophages were pre-treated with PERK inhibitor GSK2606414 before infection. FINDINGS:Our studies in RAW macrophages showed that induction of host UPR against L.donovani infection activates Akt mediated pathway which delays apoptotic induction of the host. Moreover, Leishmania infection results in phosphorylation and activation of host PERK enzyme and increased transcription of genes of inhibitor of apoptosis gene family (cIAP) mRNA. In our inhibition studies, we found that inhibition of infection induced PERK phosphorylation under apoptotic inducers reduces the Akt phosphorylation and fails to activate further downstream molecules involved in protection against apoptosis. Also, inhibition of PERK phosphorylation under oxidative exposure leads to increased Nitric Oxide production. Simultaneously, decreased transcription of cIAP mRNA upon PERK phosphorylation fates the host cell towards apoptosis hence decreased infection rate. CONCLUSION:Overall the findings from the study suggests that Leishmania modulated host UPR and PERK phosphorylation delays apoptotic induction in host macrophage, hence supports parasite invasion at early stages of infection.